Regional disparities in antenatal care utilization among pregnant women and its determinants in Ethiopia - Awoke, Nefsu; Ababulgu, Sabit Abazinab; Hanfore, Lolemo Kelbiso; Gebeyehu, Eyasu Gambura; Wake, Senahara Korsa (Frontiers in Global Women's Health, 2024)
Background: Antenatal care primarily focuses on health care checkups, the provision of advice on healthy behaviors, and the delivery of psychological, social, and emotional support for women with pregnancy. The national target set by the Ethiopian government is to achieve 95% of at least four ANC visits. Nevertheless, 43.11% of women had four or more checkups, according to the 2019 Ethiopian Demographic and Health Survey. Despite this achievement, antenatal care visits differ significantly between Ethiopian regions. Consequently, the purpose of this study was to assess regional disparities in pregnant women's utilization of antenatal care and its determinants in Ethiopia.We have used 2019 intermediate Ethiopian Demographic and Health Survey data for analysis. The analysis comprised a total of 3917 6.6 weighted women age 15-49 who had a live birth in the 5 years preceding the surveypregnant women. Poisson regression analysis was done using SAS software version 9.4. To show the strength and direction of the association, an incidence rate ratio with a 95% confidence interval was used. Variables with a p-value < 0.05 were declared as significant factors associated with the number of ANC visits.In Ethiopia, the number of ANC visits differs between regions. With a mean of 4.74 (95% CI: 4.49, 4.99), Addis Ababa reported the highest percentage of ANC visits (82.7%), while the Somali Region reported the lowest percentage (11.3%) with a mean of 0.73 (95% CI: 0.57, 0.88).Maternal age, educational level, religion, household wealth index, place of delivery, and household size show significant associations with the number of antenatal care visits.In Ethiopia, there is the highest regional disparity in the number of ANC visits. The number of ANC visits was influenced by the mother's age, education, religion, household wealth index, place of delivery, and household size. Regarding the ANC visits, there should be initiatives that address the demands of pastoralist and agro-pastoralist communities to increase ANC utilization. As with many other health outcomes, education and low socio-economic status were associated with low ANC visit but these are tied to the overall social development of a country and are not immediately amenable to public health interventions